The Resilience of Local Population in the Tourist Area of Le Thuy, Quang Binh, Vietnam: Insights from the 2024 Trami Tropical Storm - Luong, Thi Duyen; Dinh, Nhat Quang; Rizza, Caroline (Proceedings of the International ISCRAM Conference, 2025)
This paper focuses on the community resilience dimension and the potential of information and communication technology (ICT) in enhancing crisis communication in the tourist area of Le Thuy district, Quang Binh province (Vietnam) based on their experience of the Trami storm in October 2024. A case study has been conducted and relies on two five-day-field-trips (including observation and interviews) before (July) and after the storm (December) and an online ethnography. We aimed to understand how ICT has supported crisis managers, local authorities and people (including tourists) to spread and get relevant information, communicate and organize at the time of the storm. Preliminary results indicate that the community of the Province demonstrated an accurate risk acculturation based on the 2020 historical floods and relevantly combined both traditional and digital channels to prepare and respond to the floods. Lastly, the results question the relevance of mobile applications in enhancing flood prevention for remote areas.